2016
DOI: 10.1038/jhh.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure-to-height ratio as a screening indicator of elevated blood pressure among children and adolescents in Chongqing, China

Abstract: We aimed to evaluate the performance of blood pressure-to-height ratio (BPHR) and establish their optimal thresholds for elevated blood pressure (BP) among children aged 6 to 17 years in Chongqing, China. Data were collected from 11 029 children and adolescents aged 6-17 years in 12 schools in Chongqing according to multistage stratified cluster sampling method. The gold standard for elevated BP was defined as systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) ⩾95th percentile for gender, age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…This study showed that BPHR ratios are a simple and accurate method of diagnosing high values of blood pressure. The findings are in agreement with the previous studies on this matter [8,[11][12][13][14][15]28], which demonstrated the feasibility and accuracy of the SBPHR and DBPHR for screening elevated BP/HTN. The optimal cutoffs of SBPHR for defining elevated BP were 0.79 for boys and 0.80 for girls, and for defining HTN were 0.83 for boys and 0.82 for girls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study showed that BPHR ratios are a simple and accurate method of diagnosing high values of blood pressure. The findings are in agreement with the previous studies on this matter [8,[11][12][13][14][15]28], which demonstrated the feasibility and accuracy of the SBPHR and DBPHR for screening elevated BP/HTN. The optimal cutoffs of SBPHR for defining elevated BP were 0.79 for boys and 0.80 for girls, and for defining HTN were 0.83 for boys and 0.82 for girls.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Lu et al [11] developed a novel criterion, using ratios of systolic BP to height and diastolic BP to height to identify HBP. Since then, this new criterion has been used in several studies in the world [12][13][14][15] demonstrating high specificity and sensitivity from cutoff points determined by receiver operating characteristic (ROC) curves.…”
Section: Introductionmentioning
confidence: 99%